Application of Synbiotics Lactobacillus Casei and Banana Peel Waste to Improve Growth Performance of African Catfish Clarias Gariepinus in Intensive Aquaculture Systems - Linuwih Aluh Prastiti; Qorie Astria; Nadisa Theresia Putri; Dian Febriani; Rio Yusufi Subhan (Universitas Islam Lamongan, 2026)
Food security and malnutrition remain global challenges, requiring sustainable food production strategies such as the Blue Transformation concept promoted by FAO. African catfish (Clarias gariepinus) is an important aquaculture commodity for fulfilling nutritional needs, containing 19.03% protein, 8.1% fat, and high levels of essential amino acids. However, intensive farming systems often encounter constraints such as high feed conversion, reduced water quality, and suboptimal growth performance. Synbiotics, combining probiotics and natural prebiotics, offer a promising alternative to antibiotic use in aquaculture. In this context, the utilization of locally available banana peel waste as a prebiotic represents an eco-friendly approach that supports resource efficiency within the Blue Transformation framework. This study aimed to evaluate the effect of dietary synbiotics consisting of Lactobacillus casei and banana peel–based prebiotics on the growth performance and feed efficiency of African catfish. Four treatments were applied: a control diet (without synbiotics) and diets supplemented with 1%, 2%, and 3% (v/w) fermented banana peel prebiotics. Observed parameters included Specific Growth Rate (SGR), Feed Conversion Ratio (FCR), feed efficiency, and survival rate. The results indicated that synbiotic supplementation positively influenced growth and feed utilization. The best performance was obtained at the 3% dose, with an SGR of 6.78%, FCR of 1.07, feed efficiency of 93,97%, and survival rate of 84%. These findings suggest that the application of synbiotics at an optimal dose can be practically implemented in intensive African catfish culture to reduce feed costs, improve production efficiency, and support more sustainable aquaculture practices